Technical properties of the blended cements containing limestone pozzolana, and slag - Hammal, Abdulrazzaq; amino, moha (Journal of King Abdulaziz University: Science, 2024)
according to the European Standard EN 197-1, there are beside CEM I another types of cement CEM II, CEM III, CEM IV, and CEM V. This main types of cement contains in addition to clinker, another main constituent or more (pozzolanic, autopozzolanic, and fillers). The aim of the present research work was to study the validity of local raw materials and industrial wastes (limestone, pozzolana and slag) from different areas in Syria as a cement main constituents for production of the blended cements. For that purpose, the investigate was to study the effect of the mineral additions as partially substituted of clinker Portland cement on the: •Grindability performance. •Physico-mechanical characteristics. The tests and the analyses carried out on the produced blended cements showed results satisfactory, Portland-slag cement present of good technical properties, therefore it is recommended to use it in the works massive and constructions of the stoppings and maritime. Cement with the pozzolana him also present of good technical properties and has a good behavior similar that of cement to the slag, and one can use it in the maritime constructions. These tests enabled us to highlight the use of the local materials raw and industrial as additions for production of the blended cements